Expression of the ech42 (endochitinase) gene of Trichoderma atroviride under carbon starvation is antagonized via a BrlA-like cis-acting element - Brunner, Kurt; Montero, Manuel; Mach, Robert L.; Peterbauer, Clemens K.; Kubicek, Christian P. (FEMS microbiology letters, 2003)
Abstract Expression of the endochitinase encoding ech42 gene of the mycoparasite Trichoderma atroviride is subject to control by several environmental signals, including derepression by carbon starvation. In order to identify promoter areas involved in control by this condition, we prepared fusions of several mutant forms of the ech42 promoter to the Aspergillus niger goxA gene as a reporter. Removal of a 130-bp fragment comprising a binding site for the carbon catabolite repressor Cre1, an AGGGG element and three separate binding sites identical and highly similar, respectively, to those for the Aspergillus nidulans regulator of conidiation BrlA resulted in a three-fold increase in derepression under carbon starvation. A truncation of the promoter to 196 bp, which removed all of the observed DNA binding motifs, resulted in five-fold derepression. In vitro protein–DNA binding analyses showed that only the BrlA-like sites, but neither the AGGGG element nor the Cre1 binding site, bound proteins from cell-free extracts from carbon-starved mycelia of T. atroviride. Thus this study identifies a new regulator of chitinase gene expression in Trichoderma, a BrlA-like binding motif.